A clubroot pathogen effector targets cruciferous cysteine proteases to suppress plant immunity. Issue 1 (1st January 2021) - Pérez-López, Edel; Hossain, Md Musharaf; Wei, Yangdou; Todd, Christopher D.; Bonham-Smith, Peta C
ABSTRACT: Plant pathogen effector proteins are key to pathogen virulence. In susceptible host Brassicas, the clubroot pathogen, Plasmodiophora brassicae, induces the production of nutrient-sink root galls, at the site of infection. Among a list of 32 P. brassiae effector candidates previously reported by our group, we identified SSPbP53 as a putative apoplastic cystatin-like protein highly expressed during the secondary infection. Here we found that SSPbP53 encoding gene is conserved among several P. brassicae pathotypes and that SSPbP53 is an apoplastic protein able to directly interact with and inhibit cruciferous papain-like cysteine proteases (PLCPs), specifically Arabidopsis XYLEM CYSTEINE PEPTIDASE 1 ( At XCP1). The severity of clubroot disease is greatly reduced in the Arabidopsis xcp1 null mutant ( At Δ xcp1 ) after infection with P. brassicae resting spores, indicating that the interaction of P. brassicae SSPbP53 with XCP1 is important to clubroot susceptibility. SSPbP53 is the first cystatin-like effector identified and characterized for a plant pathogenic protist.